Leaders, Riverboat Gamblers, or Purposeful Unintended Consequences in the Management of Complex, Dangerous Technologies - Osborn, Richard N.; Jackson, Daniel H. (Academy of Management Journal, 1988)
Utilities' investment in nuclear-generating technology and prior earnings growth were used to predict variations in three measures of plant-operating safety. The pattern of results is consistent with three interpretations: (1) some historically successful utilities that are heavily committed to nuclear power provide leadership; (2) such utilities are gambling with public safety: and (3) a general pattern of purposeful unintended consequences arising from ignorance and self-serving myths combined with the risk propensities of executives and leading to hitherto unidentified threats to public safety.